In Silico Study of Bioactive Compounds of Betel (Piper Betle) as Antidiarrhea Assisted by Liquid Chromatography – Mass Spectroscopy - Khrisna Cendekiawan; Kintoko Kintoko; Sapto Yuliani; Linda Suci Anggraeni; Lailatul Fitria Ningrum; Siti Nur Hasana; Firda Aprillia Wardhani (Jurnal Kesehatan dr. Soebandi, 2025)
Diarrhea is a condition where feces are produced that are abnormal or not as usual. . The betel plant (Piper betle L.) is a plant that creeps, climbs and has woody bushes at the base and has a length of up to 15 m. The aim of this research is toexploring the active compounds in methanol extract of the betel plant (Piper betle)The main content that is useful as an antidiarrheal includes flavonoids, tannins, essential oils and alkaloids, where flavonoids, especially quercetin, can inhibit the release of acetylcholine and intestinal contractions.The research stages of the analysis of the potential of compounds in betel leaves (Piper betle) in silico consist of ligand preparation, receptor preparation, Lipinski prediction, and amino acid interactions. The software used is the PubChem website, rscb, while the software is Autodock Tools, and Discovery Studio Client 4.1. The results of the study showed thatThe binding energy value of quercetin can be said to be good, namely -9.72.For the interaction of quercetin amino acid residues, there is a similarity, namely located at VAL:209 with the native ligand.Besides thatThe RMSD value of the native ligand is 1.83 Å. This study concludes that quercetin meets the criteria as a candidate compound for antidiarrhea drugs contained in betel leaves.